Characteristics of Teaching the Subject of Electricity Supply on the Basis of Interactive Methods - Nurov Xomid; Amrullayev Behzod; Do‘stov Feruz (Periodica Journal, 2022)
The article examines the specifics of teaching the science of power supply based on interactive methods
Keywords: interactive; method; power source